Teorias de gauge a la Utiyama - Acevedo, O.a.; Cuzinatto, R.r.; Pimentel, B.m.; Pompeia, P.j. (Sociedade Brasileira de Física, 2018)
Abstract We review the construction of the gauge theory for semi-simple Lie groups by Utiyama in “Invariant Theoretical Interpretation of Interaction”[1]. It is shown an auxiliary fieldA μ ax must be introduced in order to keep the system of fieldϕ Ax invariant under a transformation group depending onn parameterϵ ax. This auxiliary field interacts withϕ through the covariant derivative∇ μϕ A. We determine the transformation law for A μ a under the x μ-dependent Lie group and calculate the field strengthF μ ν ax. Moreover, we specify the conserved current Ja μ related to the invariance of the complete system. The paper ends with the application of the general theory to the cases of the charged particle in an electromagnetic field and of the Yang-Mills potential under isotopic spin space transformations; we briefly address the matter of the gravitational field as a gauge theory; finally, we comment on the extension of Utiyama's theory forL A =L A A μ a ;∂ νA μ a ;∂ ρ∂ νA μ ax.

Resumo Revisamos a construção da teoria de gauge para os grupos de Lie semi-simples realizada por Utiyama em seu trabalho “Interpretação da Interação por Invariância Teórica”[1]. Mostramos que para manter a invariância de um sistema de campoϕ A( x ) sob um grupo de transformações an parâmetroϵ a( x ) dependentes do ponto x μ é necessário introduzir um novo campoA μ a( x ). Este campo auxiliar interage comϕ como manifesto pela derivada covariante∇ μϕ A. Determinamos a lei de transformação de A μ a sob o grupo mencionado e calculamos o tensor intensidade de campoF μ ν ax. Especificamos, ainda, a corrente conservada Ja μ associada à invariância do sistema completo. Encerramos aplicando a teoria aos casos da partícula carregada em um campo eletromagnético e do potencial de Yang-Mills sob transformações de um campo de spin isotópico; fazemos breves comentários sobre o campo gravitacional como teoria de gauge e sobre a extensão da teoria de Utiyama na situação em queL A =L A A μ a ;∂ νA μ a ;∂ ρ∂ νA μ ax.
Gauge theories a la Utiyama
Keywords: gauge theories; Utiyama method; teorias de gauge; método de Utiyama